(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
Poor water solubility of pharmaceutical candidates creates a big barrier to development and clinical applications. In this study, glipizide as a poorly water soluble drug was precipitated as nanoparticles and processed by spray drying to produce fast dissolving powders. Nanosuspensions of glipizide were prepared using the sonoprecipitation technique in the presence of selected stabilizers. Sorbitol, mannitol, and microcrystalline cellulose (Avicel) were involved in the formulations as the carrier of drug nanoparticles for spray drying process. Physicochemical characteristics of nano and microparticles were determined as well as maximum saturation solubility and dissolution profile of processed powders.The screening data introduced the sodium lauryl sulfate as the better nanosuspension stabilizer. Particle size and yield of nanosuspension formulations were in the range of 262.2–498.8 nm and 65.50–95.21%, respectively. The particle sizes of spray dried powders were between 2.27 μm and 29.25 μm and dissolution of the drug from these micropaticles 58.45–81.65% during the first 5 min. Spray drying of glipizide nanosuspension would be a promising approach to enhance drug solubility as well as physicochemical properties. Key words: Avicel, glipizide, nanosuspension, spray drying, sugar carrier